Magnum Streetwise - McLaren, Stephen (London : Thames & Hudson Ltd., 2022)
Abbas ; Anderson, Christopher ; Arthur, Olivia ; Barbey, Bruno ; Bendiksen, Jonas ; Berry, Ian ; Cartier-Bresson, Henri ; Davidson, Bruce ; De Keyzer, Carl ; Depardon, Raymond ; Economopoulos, Nikos ; Erwitt, Elliott ; Freed, Leonard ; Gilden, Bruce ; Gruyaert, Harry ; Harvey, David Alan ; Hurn, David ; Kalvar, Richard ; Larraín, Sergio ; List, Herbert ; Manos, Constantine ; Meiselas, Susan ; Morath, Inge ; Parke, Trent ; Parr, Martin ; Pinkhassov, Guergui ; Steele-Perkins, Chris ; Tavakolian, Newsha ; Van Agtmael, Peter ; Webb, Alex
boek